2023
DOI: 10.1029/2023gl105017
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Mantle Discontinuities From Teleseismic Body‐Wave Microseisms

S. Kato,
K. Nishida

Abstract: Ocean swell activities excite body‐wave microseisms that contain information on the Earth's internal structure. Although seismic interferometry is feasible for exploring structures, it faces the problem of spurious phases stemming from an inhomogeneous source distribution. This paper proposes a new method for inferring seismic discontinuity structures beneath receivers using body‐wave microseisms. This method considers the excitation sources of body‐wave microseisms to be spatially localized and persistent ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Both Nishida and Takagi (2022) and Zhang et al (2023) provide catalogs of events radiating significant P-waves in the secondary microseismic period band (3-10 s). The receiver-function imaging study in Japan by Kato and Nishida (2023) recently showed such a catalog's value for imaging applications. We decided to probe a "weather bomb", which occurred in southern Greenland from 8 to 11 December 2014.…”
Section: Case Study: a Major Weather Bomb Eventmentioning
confidence: 99%
“…Both Nishida and Takagi (2022) and Zhang et al (2023) provide catalogs of events radiating significant P-waves in the secondary microseismic period band (3-10 s). The receiver-function imaging study in Japan by Kato and Nishida (2023) recently showed such a catalog's value for imaging applications. We decided to probe a "weather bomb", which occurred in southern Greenland from 8 to 11 December 2014.…”
Section: Case Study: a Major Weather Bomb Eventmentioning
confidence: 99%